PENGAWASAN LIMBAH HOME INDUSTRI SAGU OLEH DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN DI DESA TELUK SUNGKA KECAMATAN GAUNG ANAK SERKA(GAS) KABUPATEN INDRAGIRI HILIR - Ferdi Pradana Jarkasih; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The development of the Indutrial sector also has a negative impect. The important of supervision of sago industry is carried out to protect the environment so that it is free from pollution that can detrimental. Environmental pollution carrieot by sago industry that occured in the area in Teluk Sungka village, Gaung Anak Serka District, Indragiri Hilir District. Environmental office has not been maximized. The purpose of this research is to see how the supervision of enviromental pollution and any factors that become a barrier to the supervision of pollution by the enviromental Indragiri Hilir District. The research was conducted using qualitative descriptive method data collected through observition and interview. The theory used in this study is Manullang theory in which a good oversight step is to determine the standars of supervision, conduct research in to surveillance objects, and perform corrective or sanctions action again breach of provisions. The result of this study indicate that pollution control by enviromental agency is not optimal, the lack of time standar in conducting direct supervision to the field is considered ineffective and also inhibiting factor in enviromental pollution monitoring conducted by the enviromental agency downstream is in terms of expert the number of supervisor, equipment assignments and operational costs. Keyword: Supervision, Enviromental Pollution, Enviromental Agency.